O metamétodo K-pop : comunicação, entretenimento e prossumo - Brito, Quise Gonçalves (2020)
K-pop is a complex cultural, communicational and marketing phenomenon. The unprecedented shift to the east that it has promoted at the center of the global media mainstream in recent years makes K-pop a fundamental and privileged object for analyzing the contemporary flows and dynamics of culture in its interface with new information and communication technologies (NTIC) and neoliberal capitalism. If K-pop emerges as a musical genre in South Korea in the mid-1990s, the turn to the second decade of the 21st century will trigger a series of changes that result in its phenomenological reconfiguration in an entertainment metamethod. To observe the process that leads to the transformation from the musical genre to the phenomenon, that is, to the entertainment metamethod, is to look at the very processes of globalization and globalization of culture from a specific window, located in Korea but in a virtual and permanent dialogue with the world. Immersed in the virtuality of the consumption of this reinvented Kpop as an interactive and self-referenced hypersystem of entertainment, its prosumers work hard in the production of agencies, assuming the role of co-authors of the phenomenon. Productivity and entertainment completely infiltrate each other this subtle, highly effective and complex system where success and failure, rather than market chance, are the product of an openly shared responsibility among fans, artists and cultural agents.